2008
DOI: 10.1002/crat.200711084
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation and microindentation analysis of vapour grown Bi2Te3‐xSex whiskers

Abstract: The structural defects and microhardness of Bi 2 Te 3-x Se x whiskers (x = 0, 0.2 and 0.4 at % Se) grown by physical vapour deposition (PVD) method have been investigated. Concentric pairs of dislocation loops were observed on the as-grown surfaces of short hexagonal prisms. A systematic study of dislocations in these crystals was carried out by chemical etching technique. The effects of Se doping, annealing and quenching on the mechanical properties have also been studied on the prism faces of Bi 2 Te 3-x Se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The degree of supersaturation plays an important role in the growth mechanism and morphology of crystals grown from vapour [8]. In the sublimation method, the transport rate enhances with ΔT = T S -T G, and a high value of the transport rate generally coincides with a high value of supersaturation [23,24]. Thus, qualitatively, supersaturation increases as ΔT increases.…”
Section: Resultsmentioning
confidence: 88%
“…The degree of supersaturation plays an important role in the growth mechanism and morphology of crystals grown from vapour [8]. In the sublimation method, the transport rate enhances with ΔT = T S -T G, and a high value of the transport rate generally coincides with a high value of supersaturation [23,24]. Thus, qualitatively, supersaturation increases as ΔT increases.…”
Section: Resultsmentioning
confidence: 88%
“…The results of crystal growth experimental trials performed for each sulfur composition are presented in Table 1. Generally, platelet and needle like crystals are the most observed morphologies of group V-VI semiconducting crystals [13,14]. But, in the present work, all the Sb 2 Te 3 À x S x compounds were crystallized in the form of platelets at the tapered end of the ampoule after a growth period of 72 h.…”
Section: Crystal Growth Of Sb 2 Te 3 à X S X From Vapormentioning
confidence: 94%
“…This bonding becomes a cleavage plane that leads to strength reduction in the single crystal. To overcome the disadvantages presented by single crystals, many synthetic methods were employed to obtain Bi 2 Te 3 -based alloy bulks with higher mechanical strength and good thermoelectric properties; these methods include the Bridgman-Stockbarger method [20], equal channel angular pressing [21], hot pressing [22], hot extrusion [23,24], shear extrusion [25], and physical vapor deposition [26]. Using a two-step spark plasma sintering technique, researchers prepared textured n-type Bi 2 Te 3 with enhanced thermoelectric and mechanical properties; the authors indicated that controlling texture effectively improved the thermoelectric and mechanical properties of Bi 2 Te 3 -based materials [27].…”
Section: Bi-te Alloysmentioning
confidence: 99%